Allosteric interactions and the modular nature of the voltage- and Ca(2+)-activated (BK) channel - Latorre, Ramon (Blackwell Science Inc, 2010)
The high conductance voltage- and Ca(2+)-activated K(+) channel is one of the most broadly expressed channels in mammals. This channel is named BK for ‘big K’ because of its single-channel conductance that can be as large as 250 pS in 100 mm symmetrical K(+). BK channels increase their activity by membrane depolarization or an increase in cytosolic Ca(2+). One of the key features that defines the behaviour of BK channels is that neither Ca(2+) nor voltage is strictly necessary for channel activation. This and several other observations led to the idea that both Ca(2+) and voltage increase the open probability by an allosteric mechanism. In this type of mechanism, the processes of voltage sensor displacement, Ca(2+) binding and pore opening are independent equilibria that interact allosterically with each other. These allosteric interactions in BK channels reside in the structural characteristics of the BK channel in the sense that voltage and Ca(2+) sensors and the pore need to be contained in different structures or ‘modules’. Through electrophysiological, mutagenesis, biochemical and fluorescence studies these modules have been identified and, more important, some of the interactions between them have been unveiled. In this review, we have covered the main advances achieved during the last few years in the elucidation of the structure of the BK channel and how this is related with its function as an allosteric protein.